2016
DOI: 10.1186/s12917-016-0785-6
|View full text |Cite|
|
Sign up to set email alerts
|

Serological response and protection level evaluation in chickens exposed to grains coated with I2 Newcastle disease virus for effective oral vaccination of village chickens

Abstract: BackgroundConventional Newcastle disease (ND) vaccination strategies in village chicken production settings is impractical due to shortage of cold-chain, unsuitability of vaccine administration routes and demanding trained personnel and hence affected its adoption. Results from earlier works elsewhere showed that the heat stable vaccines such as NDI2 are thought to be promising for village chickens. This study investigated the suitability and efficacy of Ethiopian cereal grains as carriers for the orally admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 21 publications
3
32
0
Order By: Relevance
“…This finding is equally in agreement with the finding of Wambura et al [13] where it was suggested that NDVI-2 vaccine can confer protection for up to 8 weeks. Thus, as observed by Abdi et al [22] it is recommended that repeated vaccinations induces progressively higher HI antibody titers that could correspond to high levels of protection; though repeated administration was not studied, our finding suggest a repeat administration of NDVI-2 vaccine between week 6 and week 8 postvaccination. Current conventional vaccination programs for ND virus include the use of either low-virulent live-virus vaccines or inactivated vaccines to induce protective immunity while producing minimal adverse effects in birds [23].…”
Section: Discussionsupporting
confidence: 63%
“…This finding is equally in agreement with the finding of Wambura et al [13] where it was suggested that NDVI-2 vaccine can confer protection for up to 8 weeks. Thus, as observed by Abdi et al [22] it is recommended that repeated vaccinations induces progressively higher HI antibody titers that could correspond to high levels of protection; though repeated administration was not studied, our finding suggest a repeat administration of NDVI-2 vaccine between week 6 and week 8 postvaccination. Current conventional vaccination programs for ND virus include the use of either low-virulent live-virus vaccines or inactivated vaccines to induce protective immunity while producing minimal adverse effects in birds [23].…”
Section: Discussionsupporting
confidence: 63%
“…These are the ways that enable to reduce or limit the contact of susceptible chicken with the virus by doing so it limits the spread of the disease (Abdi et al, 2016). The implementation of these measures largely depends on the degree of awareness of the personnel involved and facilities available.…”
Section: Sanitation and Management Measuresmentioning
confidence: 99%
“…Currently, in Ethiopia, four types of ND vaccine (HB1, Lasota, thermostable and IOE ND vaccine) have been produced. Although the conventional vaccines locally produced are effective to control Newcastle disease under commercial farms, they require cold chain from their production up to the administration to individual birds and handing of each bird, these, therefore limit their extensively use in village chicken (Abdi et al, 2016;Terfa et al, 2018). It should be also noted conventional vaccine application to individual birds mainly via the ocular or oral route, whereas the inactive type of vaccine is given through injection to individual birds, sub-cut is at the back of the neck or intramuscularly in the breast muscle (Mustafa and Ali, 2005).…”
Section: Vaccination Programmentioning
confidence: 99%
See 1 more Smart Citation
“…The original article [1] contains an error in the author list that was carried forward by the production team handling this article.…”
Section: Erratummentioning
confidence: 99%